"Food unites us… not anymore!?" Indonesian pilgrims eating kosher and halal in Jerusalem. (8th August 2022) - Lücking, Mirjam
ABSTRACT: Eating good Asian food is important to Indonesians who travel in religious package tours to Jerusalem. Those Indonesians who travel to Jerusalem are mainly members of Indonesia's Christian minority of around 26 million people. Only recently Jerusalem has also become a popular destination among the Muslim majority of Indonesia. Among Israelis and Palestinians who work in the tourism industry, Indonesians are known for their culinary preferences. They make sure that their customers will be satisfied with plain white rice and spicy Asian dishes. New demands for halal and kosher food challenge existing structures in the tourism sector in Jerusalem and reveal the shifting politics of eating religiously in Indonesia. Culinary controversies concern claims of a joint Indonesian culinary heritage in contrast to exclusively Muslim (and to some extent Christian) food and food spaces. Indonesians engage with global lines of conflict and bring their ideas of halal and kosher to tourist spaces in the Middle East. However, the question of taste lastly challenges the political narratives.